The Marketing Customer interface 2002-2003 - Phipps, Rosemary (Butterworth Heinemann, 2002)
Butterworth-Heinemann's 2002-2003 CIM Coursebook series offers you the complete package for exam success. Comprising the fully updated coursebook texts and free online access to the MarketingOnline learning interface, it offers everything you need to keep you on course!